Ответы и объяснения

2014-01-13T17:18:44+00:00
1)  (х-1)х(х+1)(х+2)=24                              2)(х+1)(х+2)(х+3)(х+4)= 120
х-1+2х+х+х+2=24                                        х+1+х+2+х+3+х+4=120        
х+2х+х+х=1+24-2                                        х+х+х+х=120-1-2-3-4
5х=23                                                          4х= 110
х=23: 5                                                        х= 110: 4
х= 4,6                                                          х=27,5